2022
DOI: 10.3390/pathogens12010032
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Virulence Factors during Trypanosoma cruzi Differentiation

Abstract: Chagas disease is a neglected tropical disease caused by Trypanosoma cruzi. This protozoan developed several mechanisms to infect, propagate, and survive in different hosts. The specific expression of proteins is responsible for morphological and metabolic changes in different parasite stages along the parasite life cycle. The virulence strategies at the cellular and molecular levels consist of molecules responsible for mediating resistance mechanisms to oxidative damage, cellular invasion, and immune evasion,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 131 publications
0
3
0
Order By: Relevance
“…TcUBP1 functions by stabilizing or destabilizing myriad mRNAs, depending on the interaction with other stage-specific components of ribonucleoprotein complexes throughout the parasite life cycle [10]. Our previous findings revealed that overexpression of TcUBP1 in insect-dwelling epimastigotes enhanced the abundance of TcS transcripts and altered their subcellular localization to a perinuclear region [36, 44]. These observations were further supported by a shift toward mRNA expression characteristic of infective trypomastigotes [16, 36].…”
Section: Discussionmentioning
confidence: 88%
“…TcUBP1 functions by stabilizing or destabilizing myriad mRNAs, depending on the interaction with other stage-specific components of ribonucleoprotein complexes throughout the parasite life cycle [10]. Our previous findings revealed that overexpression of TcUBP1 in insect-dwelling epimastigotes enhanced the abundance of TcS transcripts and altered their subcellular localization to a perinuclear region [36, 44]. These observations were further supported by a shift toward mRNA expression characteristic of infective trypomastigotes [16, 36].…”
Section: Discussionmentioning
confidence: 88%
“…Genetic manipulation of T. cruzi is most frequently performed in the epimastigote replicative stage. Therefore, the inclusion of histone H4 intergenic sequence allows to target, for endogenous tagging, any gene of interest even those that are not physiologically expressed in the insect form such as several mammalian host-associated virulence factors [ [46] , [47] , [48] ].…”
Section: Discussionmentioning
confidence: 99%
“…TcUBP1 functions by stabilizing or destabilizing myriad mRNAs, depending on the interaction with other stage-specific components of ribonucleoprotein complexes throughout the parasite life cycle [ 10 ]. Our previous findings revealed that overexpression of TcUBP1 in insect-dwelling epimastigotes enhanced the abundance of TcS transcripts and altered their subcellular localization to a perinuclear region [ 36 , 46 ]. These observations were further supported by a shift toward mRNA expression characteristic of infective trypomastigotes [ 16 , 36 ].…”
Section: Discussionmentioning
confidence: 99%